Production of Soap Utilizing Banana and Orange Peel Ash as Alkaline Sources - Adnan, Ahmad Khairul Amirin; Mohamad Jiwa, Mohamad Aiman; Mohd Hairuni, Muhammad Zulhelmy; Ahmad Nordin, Norain (Multidisciplinary Applied Research and Innovation, 2025)
This study has addressed the environmental problem of managing agricultural wastes by producing soap from banana and orange peels ash, which serve as alternative sources of alkaline. The experimental design details the saponification of palm oil using an alkaline solution produced by ash derived from peels of banana and orange plants. The banana and orange peels were sourced from vendors, then dried and thoroughly burned to obtain the ashes. The ashes were then mixed with water and filtered. Palm oil was added to the filtrate and heated until soap formed. The soap was analyzed for pH, foamability, and total fatty matter (TFM). The soap was found to have medium to good hardness with a fine-grained texture. The pH value accounted for 9.98, while that of TFM read 44.61 %. It thus indicated a fair cleaning quality. Further research is required for the optimization of these processes and to improve the quality of soap produced.